Oil palm: territorial conflicts and resistances in María La Baja-Bolívar, Colombia - Ávila Gonzalez, Natalia Estefanía (2015)
The implementation and extent of oil palm cultivation in the municipality of María la Baja, Bolivar has emerged as one of the most serious environmental, social, economic, cultural and territorial problems for communities that settle in this territory. This model has been implemented through the territorial dispossession, violence and proletarianization of peasants and afro descendant that stay without land to cultivate for the benefit of the oil palm industry. The text has as purpose show the historical roots that have led to the current production plan, how this is implemented, and to address these threats that accompany oil palm company land acquisition and production, alternatives built from the territory. In order to do so, the argument is founded in the basic premise that this was and still is an area in constant dispute between farmers, landowners, entrepreneurs and rural communities crossed by periods of violence and exacerbation of the conflict.